2005
DOI: 10.1529/biophysj.104.047944
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Binding of Endotoxins to the Polycationic Peptides Polymyxin B and Its Nonapeptide

Abstract: The interaction between endotoxins-free lipid A and various lipopolysaccharide (LPS) chemotypes with different sugar chain lengths-and the polycationic peptides polymyxin B and polymyxin nonapeptide has been investigated by isothermal titration calorimetry between 20 and 50°C. The results show a strong dependence of the titration curves on the phase state of the endotoxins. In the gel phase (,30°C for LPS and ,45°C for lipid A), an endothermic reaction is observed, for which the driving force is an entropicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 47 publications
5
60
0
Order By: Relevance
“…Several ITC studies dealing with the binding of AMPs to LPS were reported (53)(54)(55). To keep conditions similar to those used in the biological assays, we conducted ITC measurements at a physiological temperature (38°C) at which the species of LPS used are in the liquid crystalline phase.…”
Section: Resultsmentioning
confidence: 99%
“…Several ITC studies dealing with the binding of AMPs to LPS were reported (53)(54)(55). To keep conditions similar to those used in the biological assays, we conducted ITC measurements at a physiological temperature (38°C) at which the species of LPS used are in the liquid crystalline phase.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that ITC analysis of LPS reports on the state of order of the acyl chains in lipid A. 26 The polymer interactions with LPS and LTA result in very different thermodynamic signatures.…”
Section: Low-melting Phospholipid Mixturementioning
confidence: 99%
“…This exothermic interaction is related to the electrostatic attraction between the negative charges of the LPS/Lipid A (carboxylates and phosphates) and the positive charge of the peptides. An additional, entropically governed reaction between LPS and KTP derivatives, due to the removal of the highly ordered water layer in the backbone region of LPS (Brandenburg et al 2005), is apparently much less important than the enthalpy electrostatic effect (Table 1).…”
Section: Discussionmentioning
confidence: 99%